PENERAPAN MEDIA KARTU KATA BERGAMBAR UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN DAN DAYA INGAT ANAK - Herma Yunaili; Riyanto Riyanto (DIADIK, 2020)
The purpose of this study was to describe the pictorial word card media in learning in order to improve the beginning reading skills and memory of B1 group children in Amanah Kindergarten, South Bengkulu. The research method used was collaborative CAR, which means that researchers with class teachers and peers jointly carry out learning to improve the quality or learning outcomes. The subjects in this study were 13 children in group B1 TK Amanah Bengkulu Selatan. observation sheet. Data analysis used the average, percentage and t test. The results showed that the application of pictorial word card media could improve children's beginning reading skills with the overall percentage achievement for Cycle I 70.5% with developing categories as expected, Cycle II 83.6 % with very well developed categories, and 92.6% in Cycle III with very well developed categories and children's memory abilities with the overall percentage achievement for Cycle I with developing categories according to expectations of 69.2%, Cycle II 85.2% with categories developing very well, and Cycle III 89.7% with very well developed categories